Linguistic Impoliteness in The Sociopragmatic Perspective - Kunjana Rahardi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
The discrepancy of the study of linguistic politeness and impoliteness phenonema has been pronounced in the pragmatic study. However, up to this day the study of linguistic impoliteness, particularly based on culture-specific backgrounds has not been done. This research discusses the pragmatic manifestations of linguistic impoliteness. Through this research, a detailed description of how the manifestations and intentions of the linguistic impoliteness markers would be obtained. The data was gathered by using listening and speaking methods in linguistics. The data gathered through the basic and advanced listening and speaking methods was analyzed by using the equivalence method, particularly the extra-lingual equivalence. The research results showed that the pragmatic impoliteness was classified into five categories, namely (1) face-aggravating, (2) face-loss, (3) face-playing, (4) face-threatening, (5) deliberate ignorance. Each category of the linguistic impoliteness was described in details in its impoliteness subcategories, each was determined by its pragmatic meanings and intentions.